REPRESENTASI LOCAL WISDOM DALAM TAFSIR AL-AZHAR - Faizin; Syafruddin; Sri Chalida (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2022)
This paper analyzes the representation of local wisdom of Minangkabau culture in Buya Hamka's Tafsir al-Azhar, especially in interpreting verses about oral care. Tafsir al-Azhar is a work heavily influenced by the objective reality of local wisdom and the subjective side of the author as part of Minangkabau society. This research is literature research with content analysis through Stuart Hall's representation theory. This research shows that Hamka, in the interpretation of al-Azhar, especially the verses on oral protection, represents local wisdom: reflectively, intentionally, and constructionally. Reflectively, which directly explains the meaning of the verse he is interpreting. Consciously, Hamka interprets the verse as influenced by the collective consciousness of the Minangkabau community. Meanwhile, as a constructionist, Hamka deliberately constructs Minangkabau local wisdom in practicing interpreted verses.